Más allá del derecho de autor Otros términos para debatir la propiedad intelectual - López Cuenca, Alberto; Bermúdez Dini, Renato (Open Humanities Press, 2022)
On July 1, 2020, reforms to the Federal Copyright Act (LFDA, for its acronym in Spanish) entered into force in Mexico responding to the primarily economic requirements of the renewed free trade agreement with the United States and Canada, the USMCA. Facing these reforms, a group of Mexican and international associations and individuals raised their voices due to the numerous implications that they entailed for free speech, due judicial process, access to culture and education, technological sovereignty and their environmental impact, among others. In order to trace the deep reaching that the LFDA has today to the detriment of other rights and already established practices, from the Centro Cultural de España in Mexico City we proposed to inscribe these concerns and debate them on a broader sociocultural plane, starting from four conceptual nodes: 1) native knowledges; 2) open knowledge; 3) digital selfediting and rewriting; 4) hacktivisms. This book brings together contributions from Alberto López Cuenca, Anamhoo, David Cuartielles, Diana Macho Morales, Domingo M. Lechón, Eduardo Aguado-López, Gabriela Méndez Cota, Irene Soria, Leandro Rodríguez Medina, Marla Gutiérrez Gutiérrez, Mónica Nepote, Nika Zhenya, Renato Bermúdez Dini and Víctor Leonel Juan-Martínez.